Current vaccines, experimental immunization trials, and new perspectives to control selected vector borne blood parasites of veterinary importance - Alzan, Heba F.; Mahmoud, Mona S.; Suarez, Carlos E. (Frontiers in Veterinary Science, 2024)
Parasite infections transmitted by vectors such as ticks and blood-sucking arthropods pose a significant threat to both human and animal health worldwide and have a substantial economic impact, particularly in the context of worsening environmental conditions. These infections can manifest in a variety of symptoms, including fever, anemia, jaundice, enlarged spleen, neurological disorders, and lymphatic issues, and can have varying mortality rates. In this review, we will focus on the current state of available vaccines, vaccine research approaches, and trials for diseases caused by vector-borne blood parasites, such as Babesia, Theileria, Anaplasma, and Trypanosoma, in farm animals. Control measures for these infections primarily rely on vector control, parasiticidal drug treatments, and vaccinations for disease prevention. However, many of these approaches have limitations, such as environmental concerns associated with the use of parasiticides, acaricides, and insecticides. Additionally, while some vaccines for blood parasites are already available, they still have several drawbacks, including practicality issues, unsuitability in non-endemic areas, and concerns about spreading other infectious agents, particularly in the case of live vaccines. This article highlights recent efforts to develop vaccines for controlling blood parasites in animals. The focus is on vaccine development approaches that show promise, including those based on recombinant antigens, vectored vaccines, and live attenuated or genetically modified parasites. Despite intensive research, developing effective subunit vaccines against blood stage parasites remains a challenge. By learning from previous vaccine development efforts and using emerging technologies to define immune mechanisms of protection, appropriate adjuvants, and protective antigens, we can expand our toolkit for controlling these burdensome diseases.